Epigenetic modulation of immune synaptic-cytoskeletal networks potentiates γδ T cell-mediated cytotoxicity in lung cancer - Weng, Rueyhung R.; Lu, Hsuan-Hsuan; Lin, Chien-Ting; Fan, Chia-Chi; Lin, Rong-Shan; Huang, Tai-Chung; Lin, Shu-Yung; Huang, Yi-Jhen; Juan, Yi-Hsiu; Wu, Yi-Chieh; Hung, Zheng-Ci; Liu, Chi; et al. (Nature communications, 2021)
γδ T cells are a distinct subgroup of T cells that bridge the innate and adaptive immune system and can attack cancer cells in an MHC-unrestricted manner. Trials of adoptive γδ T cell transfer in solid tumors have had limited success. Here, we show that DNA methyltransferase inhibitors (DNMTis) upregulate surface molecules on cancer cells related to γδ T cell activation using quantitative surface proteomics. DNMTi treatment of human lung cancer potentiates tumor lysis by ex vivo-expanded Vδ1-enriched γδ T cells. Mechanistically, DNMTi enhances immune synapse formation and mediates cytoskeletal reorganization via coordinated alterations of DNA methylation and chromatin accessibility. Genetic depletion of adhesion molecules or pharmacological inhibition of actin polymerization abolishes the potentiating effect of DNMTi. Clinically, the DNMTi-associated cytoskeleton signature stratifies lung cancer patients prognostically. These results support a combinatorial strategy of DNMTis and γδ T cell-based immunotherapy in lung cancer management. Gamma delta (γδ) T cells have potential for use in immunotherapy against tumours. Here, the authors demonstrate that treatment of tumours with DNA methyltransferase inhibitors modulates cytoskeleton arrangements, upregulates adhesion molecules and increases tumour killing by γδ T cells.